Rancang Bangun Aplikasi English Proficiency Test Berbasis Website UPT Pusat Bahasa UPN “Veteran” Jawa Timur - Rafli Fahreza; Mohamad Irwan Afandi; Abdul Rezha Efrat Najaf (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
The role of information systems in the form of application programs has now developed and extended to all fields, one of which is the field of education. The use of applications will be needed for the process of implementing the EPT (English Proficiency Test). The use of applications in the EPT process will provide many advantages such as ease of checking test questions, ease of managing test data, test data that is directly integrated with the database, and ease of taking tests. However, the EPT process in the Language Center Technical Implementation Unit of UPN "Veteran" East Java still uses a manual process and is less effective. So a solution is made in the form of an EPT application. This application will be built using the Laravel framework which is open source and strong server security to be able to optimize web-based applications.